Digital Business Strategy’s Optimisation Model for Differential Value Creation in the Digital Age - Okanga, Boniface (International Journal of Applied Research in Management and Economics, 2021)
In the age where every firm is digitizing, it is no longer digitisation that leverages a firm’s competitive edge. Instead, it is the know-how of digital business strategy’s optimisation which is increasingly turning into an idiosyncratic strategic value creating resource. But even if that is the case, discerning how to bolster digital business strategy’s optimisation is still a paradox as most of the previous studies have been largely fascinated with digital transformation as a driver of digitisation. As this undermines how firms can discern how to optimise their digital business strategy, it is such a paradox that this paper sought to address by exploring a model for leveraging digital business strategy’s optimisation as a driver of differential value creation. The paper uses interpretivist research paradigm, exploratory research design and qualitative research method to explore and socially construct the opinions of sixty-six digital business managers and IT managers from the energy and chemical sector about the approaches for digital business strategy’s optimisation as well as its impact on value creation and major impediments among the multinational companies in the global energy and chemical industries. The sixty-six digital business managers and IT managers were purposively drawn from eighty multinational energy and chemical companies that are operating in South Africa, Uganda and Nigeria. Apart from investment in relevant digital technologies and digital transformation, findings revealed factors that leverage or even constrain digital business strategy’s optimisation to create differential values to often arise from how the digital business strategy is crafted and utilised as well as digital skills and level of digital culture transition. Such findings contrast theories that indicated strategic levers of digital business strategy’s optimisation to include scope, scalability, speed and sources of value creation of the digital business strategy. However, in conclusion, the paper proposes an alternative digital business strategy’s optimisation model that executives can replicate as an idiosyncratic strategic value creating resource to leverage a firm’s competitiveness in the modern complex digital age.